Effect of Coping Strategies on Stress of Parent with Intellectual Disabilities Children (Asian Education Studies, 2017)
Background: Raising a child with intellectual disability is stressful for the parent because it requires an intensive physical engagement as well as coping with emotional reactions to the child’s condition. Parents have different modes of adapting to stress and demands caused by the disorder. Method: The current descriptive research design is aimed to identify existing coping strategies of parents who have children with intellectual disabilities. This study included 60 parents with intellectual disabilities children (30 mothers and 30 fathers) that were selected by random sampling. Parent's coping strategies were assessed by Collaborative Coping Strategies in Challenging Life Events (Ghobary et al., 2003) and Questionnaire on Resources and Stress (Friedrich, short form: QRS–F) was used to examine the degree of parental stress. Result: The correlation and regression analysis was used. The most of parent were used kind of coping strategies for coping with stress. Recognition of coping strategies of the parents is important and useful for the development of therapeutic interventions aimed at facilitating family adaptation in families with a child with intellectual disabilities.